Building and design of Trkalište (racetrack): From the first gallop races in 1863 through to the first football pitches in Belgrade at the beginning of the twentieth century - Pavlović Marija (Arhitektura i Urbanizam, 2017)
Building of 'Trkalište' as the first Belgrade hippodrome had a significant role in the social and sports life of the capital. A part of the city which used to be on the outskirts starts to change rapidly. With the development and expansion of sports activities in the second half of the nineteenth century Racetrack becomes progressively important, calling for building of the first significant football pitches. The paper outlines the development of the sports facilities in 'Trkalište', from the first track for the gallop races facilitated by Knez Mihailo through to the first football pitches whose building was initiated by the effort and financial means of the greatest Serbian intellectuals of the time. By chronologically analyzing every single pitch, their major architectural features become clearly noticeable. In a very short period they have transformed from disorganized fields into the architectural forms following standards of the Western world. In parallel with the development and urbanization of Belgrade between the two world wars, sports pitches in 'Trkalište' gradually give place to the Technical University, the Svetozar Marković University Library and the Serbian Archive, acquiring new and far more modern forms in the other locations. By analyzing archive materials, newspaper articles and photograph collections the degree of societal and architectural development becomes identifiable. In this respect, this paper is a contribution to the appreciation of the sports architecture which has not had a right place within the frame of the architectural heritage of the period.